2012
DOI: 10.1590/s0100-40422012000200019
|View full text |Cite
|
Sign up to set email alerts
|

Degradação fotoeletroquímica do herbicida bentazona sobre eletrodos de carbono modificados por TiO2

Abstract: Recebido em 31/3/11; aceito em 8/8/11; publicado na web em 30/9/11 PHOTOELECTROCHEMICAL DEGRADATION OF THE HERBICIDE BENTAZONE ON THE CARBON ELECTRODES MODIFIED BY TiO 2 . This work involved the study of degradation of the herbicide bentazone in aqueous solution by different routes, in order to search a method that generates safe products to the environment. It was tested electrochemical polarization methods involving positive and negative potential, irradiation with UV light and deposition of TiO 2 on the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…Fungicides pyraclostrobin + epoxiconazole promote high toxicity for the microcrustaceans Daphnia similis and the fish species tambaqui (Colossoma macropomum), both in combination and in isolation (Prestes et al, 2012(Prestes et al, , 2013. The herbicide atrazine is the one that is most detected on surface and underground waters (Mudhoo and Garg, 2011;Santos et al, 2015), and bentazon has been identified on underground waters on the states of Virginia, Missouri, California and, more recently, in Florida (Bessegato et al, 2012).…”
Section: Comparative Analysis Across Bioindicators Ecotoxicological mentioning
confidence: 99%
See 1 more Smart Citation
“…Fungicides pyraclostrobin + epoxiconazole promote high toxicity for the microcrustaceans Daphnia similis and the fish species tambaqui (Colossoma macropomum), both in combination and in isolation (Prestes et al, 2012(Prestes et al, , 2013. The herbicide atrazine is the one that is most detected on surface and underground waters (Mudhoo and Garg, 2011;Santos et al, 2015), and bentazon has been identified on underground waters on the states of Virginia, Missouri, California and, more recently, in Florida (Bessegato et al, 2012).…”
Section: Comparative Analysis Across Bioindicators Ecotoxicological mentioning
confidence: 99%
“…Among the herbicides, a atrazine (photosystem II inhibitor) has caused some environmental issues (Santos et al, 2015) due to its diversified use to control pre-and post-emergence weeds; bentazon + imazamox (inhibitor of photosystem II and the acetolactate synthase enzyme) is used to control mono and eudicotyledons during the post-emergence state (Ferhatoglu et al, 2005); and clomazone (carotenoid synthesis inhibitor), which is used doi: 10.1590/S0100-83582016340300021 to promote the loss of virtually all plant pigments (albinism) (Bessegato et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A forma comercial desse herbicida é uma mistura de dois polimorfos e até a publicação de seu trabalho apenas a estrutura cristalina de um deles 60 havia sido publicada. Em longo prazo, a utilização de bentazona pode causar efeitos danosos ao ambiente aquático por ser altamente móvel e persistente no meio ambiente 61 , estudo futuros poderão mostrar se essas novas formas sólidas são capazes de contornar ou minimizar esses efeitos. Uma oportunidade de pesquisa nessa área está na busca de novas formas sólidas do metomil, este é um inseticida da classe dos carbamatos que exibe atividade contra as principais pragas de Lepidoptera, Coleoptera, Diptera e Hemiptera, que afetam o algodão, soja, milho, frutas e vegetais.É muito tóxico para mamíferos sendo classificado pela Agência de Proteção Ambiental dos EUA como pesticida de uso restrito de Classe I.…”
Section: Inovação Na Perceptiva Ambientalunclassified
“…Outro problema é o uso indiscriminado de agrotóxicos e de fertilizantes nas lavouras [7]. O Brasil, desde a década de 70, destaca-se como um dos maiores consumidores mundiais de agrotóxicos, principalmente de herbicidas [8,9]. Para conseguir suprir as necessidades alimentícias do país o uso de [16].…”
Section: Introductionunclassified